Fractal properties of dispersion characteristics of sinusoidally rippled plasma waveguide - Lapshyn, V.I.; Stoyanov, A.F.; Tkachenko, V.I.; Tkachenko, I.V. (Вопросы атомной науки и техники, 2005)
Features of the solution of Maxwell’s equations in sinusoidally rippled waveguide with the metal walls, filled with cold plasma, are considered. The dispersion equation which gives connection between longitudinal wave number h and frequency of fluctuations of a field ω in a waveguide is received. The “dense” spectrum which appears in the cross points of plasma modes with various numbers of spatial and radial harmonics is considered. Hausdorff’s dimension for the case of equidistant distribution of forbidden bands as a function of ripple depth is constructed and the restriction for ripple depth (depth value when suggestion becomes not valid) is obtained. Розглянуто особливості рішення рівнянь Максвелла в синусоїдально гофрованому хвилеводі з металевими стінками, наповненому холодною плазмою. Отримано дисперсійне співвідношення, що дає зв'язок між подовжнім хвильовим числом h і частотою коливань поля ω в хвилеводі. Розглянуто ”щільний” спектр зон непрозорості, що виникає у точках перетину різних просторових та радіальних гармонік. Отримано розмірність Хаусдорфа у припущені, що зони непрозорості розповсюджені еквідістантно. Також отримано обмеження на глибину гофра, при якому зазначене припущення перестає бути справедливим. Рассмотрены особенности решения уравнений Максвелла в синусоидально гофрированном волноводе с металлическими стенками, наполненном холодной плазмой. Получено дисперсионное соотношение, которое дает связь между продольным волновым числом h и частотой колебаний поля ω в волноводе. Рассмотрен «плотный» спектр зон непрозрачности, возникающий в точках пересечения различных пространственных и радиальных мод. Получено значение Хаусдорфовой размерности в предположении эквидистантного распределения зон непрозрачности, также получено ограничение на глубину гофра, когда указанное предположение перестает быть справедливым.